The Influence of Trust in Fintech Platforms, Financial Literacy, and Herding Behavior on Online Investment Decisions - Restia Christianty; Novita Adam; Isma Coryanata; Noorhani Dyani Laksmi (Malaqbi Publisher, 2026)
This study aims to examine the influence of trust in fintech platforms, financial literacy, and herding behavior on online investment decisions. The research employs a quantitative approach with a cross-sectional design, collecting primary data through a structured questionnaire distributed to 200 respondents who actively use fintech platforms for investment purposes. The data were analyzed using multiple linear regression to test the proposed hypotheses. The results indicate that trust in fintech platforms, financial literacy, and herding behavior all have a significant positive effect on online investment decisions, both partially and simultaneously. Among these variables, trust in fintech platforms is found to have the strongest influence, highlighting the importance of perceived security, transparency, and reliability in shaping investor behavior. Financial literacy also plays a crucial role in enabling individuals to make informed and rational investment decisions, while herding behavior reflects the continued impact of social influence in the digital investment environment. The coefficient of determination shows that these variables explain a substantial proportion of variance in investment decisions, suggesting that both rational and behavioral factors are essential in understanding investor behavior. This study contributes to the literature on behavioral finance and fintech adoption and provides practical implications for investors, fintech providers, and policymakers in improving the quality of investment decision-making in the digital era.